Gli esametri olospondiaci nella poesia omerica - Acerbi, Vittorio (Lexis, 2023)
This contribution analyses the extremely rare occurrences in homeric poetry of wholly spondaic lines, a peculiar form of dactilic hexameter whose metra have their elementum biceps always realised by a long syllable. After examining controversial cases and stating their belonging to that category, it is worth wondering whether and when behind the use of so composed sequences of six spondees we can see the poet’s intention to give expressiveness to these lines and suggest or emphasize with them a solemn or slow rhythm, or the effort of an action.